Inaccurate Citations Are Prevalent Within Orthopaedic Sports Medicine Literature - Daniel Homeier, M.D; Mason Adams, D.O; Thomas Lynch, M.D; Daniel Cognetti, M.D (Elsevier, 2024)
Purpose: To evaluate the peer-reviewed orthopaedic sports medicine literature for reference errors within 2 high-impact journals. Methods: In total, 769 references with 1,082 in-line citations were assessed from 20 randomly selected peer-reviewed articles published in 2 high-impact orthopaedic sports medicine journals, Arthroscopy and the American Journal of Sports Medicine. Full-text copies of references were obtained through online literature subscription databases. Two investigators evaluated each citation for agreement between the reference's study design, methods, data, discussion, and conclusion with the citing authors' claims. Error rates, interobserver agreement, and association between error rates and journal demographics were assessed. Results: Cohen's κ coefficient representing interobserver agreement was 0.61. The mean citation error rate across 20 articles from 2 orthopaedic sports medicine journals was 6.6%. The most common error was failure to support the authors' assertions within the citing article, accounting for 32% of errors. There was no significant association between error rate and journal impact factor, number of cited references or total references, ratio of in-line citations to cited references (citation ratio), and number of authors. There was no significant relationship between error rate and journal, study type, and level of evidence. Conclusions: Inaccurate claims and citations are common within the orthopaedic sports medicine literature, occurring in every reviewed article and 6.6% of all in-line citations. Failure to support the assertions of the article in which a reference is cited is a common error. Authors should take care to rigorously assess references with particular attention to accurate citation of primary sources. Clinical Relevance: This study highlights the prevalence of citation errors within a random sampling of high-level orthopaedic sports medicine articles. Given science is cumulative, these errors perpetuate inaccuracies and are at odds with evidence-based practice.